2009
DOI: 10.1029/2008pa001729
|View full text |Cite
|
Sign up to set email alerts
|

Deglacial diatom productivity and surface ocean properties over the Bermuda Rise, northeast Sargasso Sea

Abstract: Diatom assemblages document surface hydrographic changes over the Bermuda Rise. Between 19.2 and 14.5 ka, subtropical diatom species and Chaetoceros resting spores dominate the flora, as in North Atlantic productive regions today. From 16.9 to 14.6 ka, brackish and fresh water diatoms are common and their contribution is generally coupled with total diatom abundance. This same interval also contains rare grains of ice‐rafted debris. Coupling between those proxies suggests that successive discharge of icebergs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 61 publications
5
48
0
1
Order By: Relevance
“…36) or from the convergence of frontal systems. Introduction of meltwater lenses during icerafting events from the North are consistent with records of smaller diatoms 7 and the deposition of ice-rafted debris at the Bermuda Rise 9 , and the onset of changes in the planktonic foraminiferal d 18 O record from HU89038-PC8 (Fig. 3).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…36) or from the convergence of frontal systems. Introduction of meltwater lenses during icerafting events from the North are consistent with records of smaller diatoms 7 and the deposition of ice-rafted debris at the Bermuda Rise 9 , and the onset of changes in the planktonic foraminiferal d 18 O record from HU89038-PC8 (Fig. 3).…”
Section: Discussionsupporting
confidence: 55%
“…18). Although there is evidence for increased diatom opal burial in the oligotrophic North Atlantic during Stadials 7 , there has been, as of yet, no quantified study of low-latitude silicon cycling during millennial-scale climatic change and its impact on carbon cycling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Heinrich events are typically identified in North Atlantic sediment cores as layers of coarse-grained lithogenic fragments most likely transported by icebergs, otherwise known as "ice-rafted debris" [Heinrich, 1988;Hemming, 2004] Th values during H1 (and also during Heinrich Events 2 and 3) correspond with peaks in diatom abundance. Likewise, Gil et al [2009] found that the high 231 Pa/ 230 Th values during H1 in OCE326-GGC5 nearly coincide with an interval of higher diatom content in a nearby core, concluding that opal productivity may have biased earlier interpretation of these values in terms of MOC.…”
Section: Introductionmentioning
confidence: 94%
“…These results appear inconsistent with 231 Th ratios from the LGM are lower than those from H1, implying a more vigorous circulation during the LGM, whereas the apparent ventilation ages imply that the H1 circulation was more vigorous. Keigwin and Boyle explained the apparent inconsistency between the two proxy records by hypothesizing that the high 231 Pa/ 230 Th observed during H1 result from high diatom (opal) fluxes, as apparently supported by diatom abundance data reported in subsequent work [Gil et al, 2009;Lippold et al, 2009]. Note that the issue of data consistency may not lie solely in reevaluating 231 Pa/ 230 Th (for a critical discussion of 14 C see, e.g., Wunsch [2003]).…”
Section: Introductionmentioning
confidence: 96%